Pengaruh Leverage, Umur Perusahaan, dan Profitabilitas terhadap Praktik Manajemen Laba : (Studi Empiris Terhadap Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Margareta Devi; Audrey Patricia Theodora (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
This study aims to analyze the effect of leverage, company’s age, and profitability towards earnings management in State Owned Enterprise that listed on Indonesia Stock Exchange in 2015-2019. The type of this research is quantitative research. Samples were collected using purposive sampling method, which resulting in 105 samples. Data analysis techniques that used in this research is multiple linear regression analysis. The result of this research shows that partially leverage and company’s age have significant effect towards earnings management. While profitability has no significant effect towards earnings management. Furthermore, leverage, company’s age, and profitability simultaneously have significant effect towards earnings management.